All Days 2000
DOI: 10.4043/12084-ms
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Dynamic Analysis of Platforms, Risers, and Moorings

Abstract: Motion analysis of platforms operating in deep waters is quite a challenge. In order to obtain a realistic motion, the analysis must be performed as an integrated system of risers, mooring lines, and the platform. A fully coupled analysis of such a system is very time consuming and modeling simplifications, both structural and hydrodynamic, are often applied thereby introducing uncertainty in the accuracy of the results. For accurate vessel motions such fully coupled analysis may not really be warranted. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some researchers investigated the coupling effect of the spar mooring system (Chaudhury 2001;Chaudhury, Ho 2000;Ding et al 2003Ding et al , 2005Garrett 2005;Koo et al 2004;Vazquez-Hernandez et al 2006). Tahar and Kim (2008) developed numerical tool for coupled analysis of deepwater floating platform with polyester mooring lines.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers investigated the coupling effect of the spar mooring system (Chaudhury 2001;Chaudhury, Ho 2000;Ding et al 2003Ding et al , 2005Garrett 2005;Koo et al 2004;Vazquez-Hernandez et al 2006). Tahar and Kim (2008) developed numerical tool for coupled analysis of deepwater floating platform with polyester mooring lines.…”
Section: Introductionmentioning
confidence: 99%
“…Based on results, it was concluded that the current drag on mooring lines and risers could be significant and should be included in the response predictions. Chaudhury and Ho [90] developed an integrated system of risers, mooring lines, and platform in ABAQUS. The dynamic equilibrium of the Spar system and non-linear soil mooring line interaction were taken into account.…”
Section: Analysis Technique Of Classic Sparmentioning
confidence: 99%